OP0012 Chronic recurrent non-bacterial osteomyelitis in danish children. (23rd January 2014) - Bech, A.Z.; Herlin, T.; Hansen, O.R.; Heuck, C.; Fiirgaard, B.
Abstract : Background: Chronic recurrent multifocal osteomyelitis (CRMO) is a non-infectious inflammatory bone disease of unknown etiology that predominantly affects children and young adults. It is characterized by multifocal inflammatory bone lesions with swelling and pain and an unpredictable course of exacerbations and spontaneous resolution. The goal of treatment is to relieve clinical symptoms. There is no known cure. Objectives: To determine the clinical outcome of children with chronic recurrent multifocal osteomyelitis (CRMO). Methods: We conducted a retrospective evaluation of children, under the age of sixteen, diagnosed with CRMO at the Department of Pediatrics, Aarhus University Hospital Skejby between January 2001 and June 2011. We found the patients by searching the database with the keyword chronic recurrent multifocal osteomyelitis (CRMO) and the ICD-code M86.3; and reviewed clinical, radiological and bone biopsy data registered in the patient's file. Results: Thirty-onepatients were assessed (19 girls and 12 boys). Mean age at disease onset was 10.3±2.6 years. Mean diagnostic delay was 17.3±15.3 months. Twenty-one (67.7%) had two or more bone lesions, ten (32.3%) had only one lesion. Conventional X-rays were performed in twenty-seven patients (87.1%); and scintigraphy in twenty-one (67.7%) (20 whole-body and 1 plantar); MRI/CT in thirty patients (96.8%) of which eight (25, 8%) had a whole-body MRI. MRI/CT discovered most lesions compared to X-ray and scintigraphy. CT descriptions more often registered sclerotic, hyperostotic and lytic lesions whereas MR description registered bone edema. The most frequent location of the bone lesions was in the lower extremities with the highest incidence in the tibia followed by the axial skeleton (column, pelvis and clavicles). In the long tubular bones the lesions were most often localized in the metaphysis. In twenty-two children bone biopsy was performed. All biopsies revealed negative bacterial cultures and chronic inflammation was most prevalently observed. Extra-osseous involvement was noted in twenty patients (64.5%) of which five (16.1%) had psoriasis and three (9.7%) had PPP. Extra-osseous involvement was noted in 64.5% with arthritis as the most common. In the multifocal group 23.8% had psoriasis and 14.3% had PPP. In the monofocal group none had psoriasis or PPP. ESR but not CRP was significantly higher in boys compared to girls. We found no significant difference in either ESR or CRP values comparing the group of patients having one lesion with the group having two or more lesions. All patients were treated with NSAIDs. Seventeen received corticosteroids (54.8%), nine MTX (29.1%), three pamidronate (9.7%) and one remicade (3.2%). The mean sum of lesions was higher in the group of patients treated with prednisolone, MTX, infliximab or pamidronate compared to the patients not receiving immunosuppressants. Conclusions: We find that patients with monofocal disease have comparable clinical, radiological and histological characteristics to those with multifocal lesions. Comparing the disease duration, equal chronicity was observed presenting similar ongoing exacerbations.We find whole-body MRI as a relevant screening instrument for the diagnosis of CRMO. Prospective, randomized controlled studies are needed to evaluate the efficacy of bisphosphonate treatment for CRMO. Disclosure of Interest: None Declared